Neo-Urban Sufisme di Kalangan Remaja: Studi Kasus Terhadap Gerakan Sosial-Spiritual Ukhsafi Copler Community di Surabaya - Syatori, Ahmad; Ahmad Syatori, Syatori (Mahad Aly Al Fithrah, 2025)
The emergence of various expressions of religious activities that have grown in the midst of urban life can be interpreted as a form of increased religiosity in the new model movement. When viewed from the perspective of the current phenomenon of urban Sufism, it is clear that there are majelis dzikir (prayer gatherings) developing in every corner of the city. These gatherings are activities organised by a group of young people and teenagers popularly known as the Ukhsafi Copler Community (UCC). The purpose of this study is to explore and reveal the socio-spiritual phenomena in the important role of UCC activities in relation to the problems of Neo-Urban Sufism among young people and teenagers in the city of Surabaya. The research method used in this study is qualitative research with a phenomenological approach, which is the science of the development of human consciousness and self-awareness. The technique used to determine the informants in this study was purposive, whereby the researcher selected various subjects based on specific reasons. This study found negative symptoms, attitudes and behaviours among young people and teenagers, including criminal acts and juvenile delinquency. The formulation of the problem regarding the origins and definition, characteristics of the UUC and its various activities was an important part of this study. The socio-spiritual movement in the activities carried out by the Ukhsafi Copler Community can have a very positive and significant impact, which is noted in the conclusions of this study.